2014
DOI: 10.1111/exd.12333
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with sodium butyrate and PD153035 enhances keratinocyte differentiation

Abstract: Epidermal growth factor (EGF) receptor (EGFR) signaling is a critical determinant of keratinocyte proliferation and differentiation in both normal and diseased skin. Here we explore the effects of combined treatment with the differentiation-promoting agent sodium butyrate (SB) and the EGFR inhibitor (EGFRI) PD153035 on terminal differentiation of normal human epidermal keratinocytes (NHEKs). Cells treated with SB showed increased expression of the levels of mRNA and protein of the differentiation markers filag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Our data confirms this report as this combination did not improve the diabetic wound closure and failed to produce additive increase in receptor protein levels ( Figures 1, 2, and 3). It has been shown that Na-Bu treatment leads to withdrawal of cells from cell cycle [28] and the current data confirms this report as Na-Bu caused less than 5% wound closure (Table 4) perhaps due to withdrawal of most cells from cell cycle at the wound site.…”
Section: Discussionsupporting
confidence: 89%
“…Our data confirms this report as this combination did not improve the diabetic wound closure and failed to produce additive increase in receptor protein levels ( Figures 1, 2, and 3). It has been shown that Na-Bu treatment leads to withdrawal of cells from cell cycle [28] and the current data confirms this report as Na-Bu caused less than 5% wound closure (Table 4) perhaps due to withdrawal of most cells from cell cycle at the wound site.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with these observations, other studies showed that treatments with HDACIs resulted in premature expression of differentiation markers. 51,52 It is also possible that HDACI effects are not limited to miR-335 regulation; SOX6 may also recruit HDACs to suppress target genes. 53 Two independent studies have demonstrated that trichostatin A may suppress the development of AD-like symptoms in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased expression levels of p52 and TGF-β were also shown suggesting the involvement of cell proliferation and terminal differentiation as well [121]. Finally, a combined treatment protocol with sodium butyrate and PD153035 (an epidermal growth factor receptor inhibitor) was shown capable of enhancing keratinocyte differentiation [123]. Collectively, data suggest that sodium butyrate can act as a potential additional approach to the management of hyperproliferative skin diseases (including psoriasis) by modulating key cellular processes like apoptosis, proliferation and differentiation (Table 2 and Figure 2).…”
Section: Psoriasismentioning
confidence: 91%